THE RELEVANCE OF THE TERM «NATIONAL BOURGEOISIE» FORRESEARCHINGTHE RULING ELITE IN UKRAINE - Ільїн, І. В. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2020)
The article demonstrates the relevance of the concept of «national bourgeoisie» in the context of researching the ruling elite in Ukraine. The main limitations of the current concepts of the Ukrainian ruling elite are an ahistorical approach, and treating it (elite) as an anomaly, pathology. Particular attention is paid to the criticism of the concepts «neopatrimonial democracy», «oligarchy», «corruption», which constitute the core contents of the current concepts of the ruling elite in Ukraine. The concept of «national bourgeoisie» and the exposition of its evolution in Marxist theory serves as the basis for the criticism. It was determined that neopatrimonialism, and with it oligarchy and corruption, are concepts denoting the power of one faction unfavorable for theother faction of the bourgeoisie. These terms do not refer to any existing norm, alternative, do not imply the opposite, its otherness (democracy, the rule of law, but they are polemical, rhetorical figures in the class struggle. The theoretical content of these concepts acquires scientific meaning only when using the Marxian concept of the bourgeoisie (or the national bourgeoisie in the Marxist tradition), which presupposesthe rule of law insofar as it meets the economic interests of the bourgeoisie, and the state is a concentrated expression of these interests, as well as a foothold in the struggle of different factions of the bourgeoisie among themselves and against the oppressed classes (hence, bourgeois democracy). Power is not conceived outside of capital since capitalists are indirectly or directly related to each other and influence the authorities’ decisions. Under the conditions of postcolonialism, or neocolonialism, the national bourgeoisie has resorted to more direct forms of protecting their interests through state, restricting foreign capital in the economy and political power. However, this does not mean the absolute independence of the national bourgeoisie from the transnational bourgeoisie, both in the political and in economic sense. The study proves the necessity of using the concept of «national bourgeoisie» for researching the ruling elite in Ukraine under capitalism in general, and the intra– and interclass struggle in particular.